Konflik Kepentingan antara Manajemen dan Pemilik Perusahaan - Yulekhah Ariyanti; Ratna Kusumawati (Universitas Wahid Hasyim, 2006)
The article explored the effect of separation between share holder and management which could make agency problem. The problem was caused by the agent and the principal as economic agent so they tried holding their interest and doing moral hazard for protecting their interest.